DEVELOPMENT OF WEBSITE-BASED INSTRUCTIONAL MEDIA TO IMPROVE VOCATIONAL HIGH SCHOOL STUDENTS LEARNING OUTCOMES IN BASIC ECONOMICS - Cecilia Azhara Ayuningtiyas; Henry Eryanto; Ria Rahma Nida (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study was motivated by the low academic achievement of 10th-grade students at SMKN 48 Jakarta in the subject of Basic Economics, with an average score of 75.71 below the minimum passing score of 82.00 as well as the limitations of conventional and less interactive learning media. The application of the ADDIE model in the Research and Development (R&D) methodology served as the basis for this study to develop web-based learning materials using the Wix platform, while also assessing their feasibility, practicality, and effectiveness. The results showed that the media achieved an average feasibility percentage of 92.89% (highly feasible), a practicality percentage of 90.48% in the one-to-one test and 93.71% in the small-group test (highly practical), and an N -Gain value of 0.54 (moderate), with an increase in the average score from 70 to 86.46. Thus, the Wix-based website learning media is deemed feasible, practical, and effective for supporting the learning of Basic Economics at vocational high schools.